Physics from the lattice: glueballs in QCD; topology; SU(N) for all N - Teper, M (1997)
Lectures given at the Isaac Newton Institute, NATO-ASI School on "Confinement, Duality and Non-Perturbative Aspects of QCD", 23 June - 4 July, 1997.